Agri-food business: global challenges - innovative solutions - Thomas Glauben; Jon H. Hanf; Michael Kopsidis; Agata Pieniadz; Klaus Reinsberg (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2008)
The rise of a western-style middle class in many successful emerging economies like China currently is inducing deep structural changes on agricultural world markets and within the global agri-food business. As a result of both higher incomes and concerns over product safety and quality the global demand for high-quality and safe food products is increasing significantly. In order to meet the new required quality, globally minimum quality standards are rising and private standards emerging. All over the world these developments cause adjustments at the enterprise, chain and market levels. At the same time, the tremendously increasing demand for renewable energy has led to the emergence of a highly promising market for biomass production. This has far-reaching consequences for resource allocation in the agri-food business, for the environment, for the poor in developing countries and for agricultural policy reforms. The challenges increase with ongoing liberalisation, globalisation and standardisation, all of which change trade patterns for agricultural and food commodities, and influence production costs and commodity prices. CONTENTS: Preface... i; On the political economy of food standards ... 1, Johan F. M. Swinnen, Thijs Vandemoortele; An analytical framework for the study of deviant behaviour in production... 11, Norbert Hirschauer, Gaetano Martino; Netchain innovations for sustainable pork supply chains in an EU Context... 22, Rannia Nijhoff-Savvaki, Jacques Trienekens, Onno Omta; Inclusion of dairy farms in supply chain in Bulgaria - Modes, efficiency, perspectives... 35, Hrabrin Bachev; The effective traceability on the example of Polish supply chain ... 47, Agnieszka Bezat, Sebastian Jarzebowski; Geographical indications in transition countries: Governance, vertical integration and territorial impact. Illustration with case studies from Serbia... 58, Marguerite Paus; Processing and marketing feasibility of underutilized fruit species of Rajasthan, India ... 70, Dheeraj Singh, Lobsang Wangshu, V. C. Prahalad; Future impact of new technologies upon food quality and health in Central Eastern European countries... 82, Lajos Zoltán Bakucs, Imre Ferto, Attila Havas; Are food industry companies interested in co-financing collective agricultural marketing?... 95, Anikó Tóth, Csaba Forgács; Farmers' reasons for engaging in bioenergy utilisation and their institutional context: A case study from Germany ... 106, Melf-Hinrich Ehlers; Degree and pattern of agro-food trade integration of South-Eastern European countries with the European Union ... 118, Štefan Bojnec, Imre Ferto; Competitiveness of cotton and wheat production and processing in Central Asia ... 133, Inna Levkovych
urn:nbn:de:gbv:3:2-10769
Keywords: 330